Cytomegalovirus Viremia Associated With Increased Mortality in Cryptococcal Meningitis in Sub-Saharan Africa. (1st September 2019) - Skipper, Caleb; Schleiss, Mark R; Bangdiwala, Ananta S; Hernandez-Alvarado, Nelmary; Taseera, Kabanda; Nabeta, Henry W; Musubire, Abdu K; Lofgren, Sarah M; Wiesner, Darin L; Rhein, Joshua; Rajasingham, Radha; Schutz, Charlotte; et al.
Abstract: Background: Cryptococcal meningitis and tuberculosis are both important causes of death in persons with advanced human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS). Cytomegalovirus (CMV) viremia may be associated with increased mortality in persons living with HIV who have tuberculosis. It is unknown whether concurrent CMV viremia is associated with mortality in other AIDS-related opportunistic infections. Methods: We prospectively enrolled Ugandans living with HIV who had cryptococcal meningitis from 2010–2012. Subsequently, we analyzed stored baseline plasma samples from 111 subjects for CMV DNA. We compared 10-week survival rates among those with and without CMV viremia. Results: Of 111 participants, 52% (58/111) had detectable CMV DNA (median plasma viral load 498 IU/mL, interquartile range [IQR] 259–2390). All samples tested were positive on immunoglobin G serology. The median CD4 + T cell count was 19 cells/µL (IQR 9–70) and did not differ by the presence of CMV viremia ( P = .47). The 10-week mortality rates were 40% (23/58) in those with CMV viremia and 21% (11/53) in those without CMV viremia (hazard ratio 2.19, 95% confidence interval [CI] 1.07–4.49; P = .03), which remained significant after a multivariate adjustment for known risk factors of mortality (adjusted hazard ratio 3.25, 95% CI 1.49–7.10; P = .003). Serum and cerebrospinal fluid cytokine levels were generally similar and cryptococcal antigen-specific immune stimulation responses did not differ between groups. Conclusions: Half of persons with advanced AIDS and cryptococcal meningitis had detectable CMV viremia. CMV viremia was associated with an over 2-fold higher mortality rate. It remains unclear whether CMV viremia in severely immunocompromised persons with cryptococcal meningitis contributes directly to this mortality or may reflect an underlying immune dysfunction (ie, cause vs effect). Clinical Trials Registration: NCT01075152. Abstract : Cytomegalovirus viremia was associated with increased mortality in persons with acquired immunodeficiency syndrome and cryptococcal meningitis. It is unclear whether cytomegalovirus reactivation is driving the hazard or is a sensitive marker of declining immune function.